The Influence of Servant Leadership and Employee Compensation on Employee Engagement Through Employee Job Satisfaction as an Intervening Variable at PT Indonesia Power Suralaya Power Generation Unit - Reinardus Dwi Prio Christianto (Journal of Business and Behavioural Entrepreneurship, 2021)
Background - Nowadays, employee engagement is a major concern for organizational leaders around the world. Human Resources (HR) is a key element of a company that will support effective and efficient organizational governance (Christian et al., 2021). However, not all employees have the same level of engagement, factors that can affect employee commitment such as motivation, job satisfaction, leadership, diversity of co-workers, organizational culture, and others (Vinsensius et al., 2019). Purpose - This study aims to analyze: (1) the magnitude of the influence of servant leadership on employee engagement, (2) the magnitude of the influence of employee compensation on employee engagement, (3) the magnitude of the influence of servant leadership on employee job satisfaction, (4) the magnitude of the effect of employee compensation on employee engagement. employee job satisfaction, and (5) the magnitude of the influence of employee job satisfaction on employee engagement at PT Indonesia Power Suralaya Power Generation Unit. Originality/value - The novelty (originality or value) of this research is that servant leadership has no effect on employee engagement and employee compensation has no effect on employee job satisfaction. Research Limitations - The limitations of this study are only to get an idea of ​​the perceptions of employees of PT Indonesia Power Suralaya Power Generation Unit regarding servant leadership, employee compensation, employee job satisfaction and employee engagement. Design/methodology/approach - The population in this study are employees of PT Indonesia Power Suralaya Power Generation Unit which is located at Jalan Raya PLTU Suralaya, Cilegon, Banten. The research method is quantitative using a questionnaire with a Likert scale and the sampling technique is done by simple random sampling. The number of samples used as many as 32 samples to test the hypothesis. Structural Equation Modeling was used to test the statistical significance of the path coefficients, and processed using the PLS Smart 3.2.9 program. Findings - The results showed that servant leadership and employee compensation affected job satisfaction by 64.9%, while employee engagement was influenced by 86.8%. This direct effect shows that servant leadership has no effect on employee engagement, employee compensation has a positive and significant effect on employee engagement, servant leadership has a positive and significant effect on employee job satisfaction, employee compensation has no effect on employee job satisfaction, and employee job satisfaction has a positive effect. and significant to employee engagement.